Radiological Consequences Modelling for a Land Based Operations Environment - Silva, Rodrigo Werner; Reis, André Luiz Queiroga; Stenders, Ricardo M.; ANdrade, Edson Ramos (Defence Science Journal, 2021)
Radiological Dispersive Devices (RDD) are often portrayed as weapons used by radical (asymmetric) forces, however they can also be used in a regular war. In this study, a hypothetical scenario where an asymmetric force contaminates the battlefield, by detonating an RDD prior to the soldier’s arrival without being detected, is simulated. The software HotSpot was used due to its speed and conservative results which can help inform the decisions made by the commanding officers. HotSpot performs a Gaussian simulation of the radioactive dispersion in the environment. The plumes that arise from the explosion are considered to be affected by the atmospheric conditions. In this study, those conditions are represented by the Pasquill-Gifford stability classes. The results of the simulation show that remaining stationary, if the contaminated area size is not affected by the PG class variation, may increase the radiological risk. It is better to move the soldiers around in order to avoid additional exposure, however that may also be a challenge for various reasons including changes in the shape of the contaminated area. Nevertheless, the variations in local PG classes gain importance as the distance from the release point increases.